Delovno mesto kot dejavnik ohranjanja in izboljševanja pismenosti - Ivančič, Angela (Družboslovne razprave, 2006)
Results of comparative research into adult literacy show that the biggest share of variance in individual literacy achievements is explained by education, age, participation in the labour force and occupational category. However, literacy skills are not only acquired in the school environment but also through the active utilisation of these skills in various environments. As adults most often use their writing, reading and calculating skills at work, the workplace is one of the most important such learning environments. This article seeks to illuminate the effect of the opportunities provided by the workplace for more diverse practices of literacy skills on individual literacy achievements by analysing the data collected in the International Adult Literacy Survey (IALS) in Slovenia and five selected European countries.It argues that in all selected countries the better education, occupational categories based on higher qualification levels and the more frequent use of more complex writing and reading practices at work point to higher levels of prose, documentary and mathematic literacy achievements.
Keywords: literacy; Pismenost; delovna sila; functional literacy; delovno mesto; manpower; place of work; vzgoja in izobraževanje; education; izobrazbena neenakost; človeški viri; izobraževanje